Instrumentalization of Judaism in the Zionist Political Discourse - Muhammad Subhan Saleem, (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
Judaism, an ancient faith rooted in monotheism, contrasts sharply with Zionism, a political movement that emerged in late 19th century. While Zionism began as a response to anti-Semitism, it evolved into a nationalist movement with significant political and socio-economic implications. The creation of the State of Israel in 1948, influenced by the Zionist agenda, provoked regional tensions and disturbed global peace in the form of the Israel-Palestine conflict. The main purpose of this article is to analyse the manipulation of Judaism by Zionism for its own political and social discourse. Data will be interpreted through the critical lens of Rational Choice Theory (RCT), which is a useful methodological approach for understanding the intersection of politics, religion and geopolitical strategy. The results of the investigation show the intricate relationship between religion and politics and demonstrate that religious narratives can be manipulated to serve broader political agendas, thereby impacting regional and global peace. In short, the analysis emphasizes the importance of distinguishing between religious beliefs and political movements in order to understand contemporary conflicts and to reduce anti-religious sentiment.